2007
DOI: 10.1007/s12016-007-8017-2
|View full text |Cite
|
Sign up to set email alerts
|

Share Epitope, Citrullinated Cyclic Peptide Antibodies and Smoking in Brazilian Rheumatoid Arthritis Patients

Abstract: The events involved in the pathogenesis of rheumatoid arthritis (RA) still remain unclear, but certainly the etiology is multifactorial. Shared epitope (SE) of HLADRbeta1 is the most important genetic risk factor. Environmental risk factors are less understood. Smoking is a candidate, associated with the rising of citrullinated cyclic peptide antibodies (anti-CCP). Anti-CCP antibodies are highly specific for RA. In this study, we investigated whether the association between anti-CCP production and smoking was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
8
0
3
Order By: Relevance
“…As reported in more homogeneously Caucasian populations5-8, we showed that SE alleles and tobacco exposure are related to anti-CCP antibodies in RA patients. Several previous studies observed these same relationships in Brazilian RA patients 34,35…”
Section: Discussionsupporting
confidence: 72%
“…As reported in more homogeneously Caucasian populations5-8, we showed that SE alleles and tobacco exposure are related to anti-CCP antibodies in RA patients. Several previous studies observed these same relationships in Brazilian RA patients 34,35…”
Section: Discussionsupporting
confidence: 72%
“…Environmental risk factors are less understood. Smoking is a candidate, associated with increased citrullinated cyclic peptide antibodies (30)(31)(32). In this study, we investigated the associations between HLA class II alleles and RA and the protective effects of the DERAA-encoding HLA-DRB1 alleles on RA susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…in association to genetic background of MHC alleles. In RA, complex environmental and genetic factors are believed to contribute to their development (Oliveira et al 2008). Human leukocyte antigen genes class II region on chromosome 6 (HLA-DRB1 alleles *0401, *0404, *0405, *0408, *0101, *0102, *1001 and *1402) have been strongly associated with susceptibility to the disease, according to the population studied (du Montcel et al 2005).…”
Section: Discussionmentioning
confidence: 99%